2020
DOI: 10.1007/978-3-030-60975-7_1
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Social Connectedness in Europe

Abstract: We use de-identified and aggregated data from Facebook to study the structure of social networks across European regions. Social connectedness declines strongly in geographic distance and at country borders. Historical borders and unions—such as the Austro-Hungarian Empire, Czechoslovakia, and East/West Germany—shape present-day social connectedness over and above today’s political boundaries and other controls. All else equal, social connectedness is stronger between regions with residents of similar ages and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Indeed, there is some evidence suggesting that such exposure may be substantial within the Balkan region. In 2016, Facebook introduced the first comprehensive measure of social connectedness across the world, constructing a dataset of aggregated information of friendship links between all Facebook users (63). Researchers have found that the level of connectedness is higher between regions who formed part of the same country in the past and highlight some regions in the former Yugoslavia as being several times more connected compared to similar pairs of other European regions (63).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is some evidence suggesting that such exposure may be substantial within the Balkan region. In 2016, Facebook introduced the first comprehensive measure of social connectedness across the world, constructing a dataset of aggregated information of friendship links between all Facebook users (63). Researchers have found that the level of connectedness is higher between regions who formed part of the same country in the past and highlight some regions in the former Yugoslavia as being several times more connected compared to similar pairs of other European regions (63).…”
Section: Discussionmentioning
confidence: 99%
“…That same survey shows that Facebook usage rates among U.S.-based online adults were relatively constant across income groups, education levels, and race, and among urban, rural, and suburban residents; usage rates were slightly declining in age (from 79% of individuals aged 18 to 29, to 46% of individuals aged 65 and older). See Allen, Peng, and Shan (2020); Bailey, Cao, Kuchler, and Stroebel (2018); Bailey, Cao, Kuchler, Stroebel, and Wong (2018); Bailey, Dávila, Kuchler, and Stroebel (2019); Bailey, Farrell, Kuchler, and Stroebel (2020); Bailey, Gupta, Hillenbrand, Kuchler, Richmond, and Stroebel (2020); Bailey, Johnston, Kuchler, Russel, State, and Stroebel (2020); Bali, Hirshleifer, Peng, and Tang (2018); Kuchler, Russel, and Stroebel (2020a); Kuchler, Peng, Stroebel, Li, and Zhou (2020); Wilson (2019) and Rehbein and Rother (2020) for other economics and finance research using data from Facebook.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Using the same data on social connectedness as used here, researchers have found that Covid-19 was more likely to spread between locations with stronger connections [24]. There is also more travel between locations which share a high social connectedness index [8]. Albeit imperfect, the comparison with Covid-19, which transmits in close physical proximity, can be informative.…”
Section: Choice Of Comparator Symptomsmentioning
confidence: 77%
“…It can be interpreted as the probability of there existing a social connection between individuals residing in two locations. In the US and Europe, the index is higher between two locations that share the same language, religion, history, and demographics such as age and education [6,8].…”
Section: Social Networkmentioning
confidence: 99%